Different binding characteristics of ciprofloxacin to iron mineral surfaces: Thermodynamic evidence and site energy distribution analysis. Issue 3 (14th April 2021) - Li, Xiangzhi; Lei, Feifei; Li, Binghua; Bi, Erping
Abstract: Iron minerals in soil play an important role in controlling the migration of fluoroquinolones. In this study, batch experiments were carried out to investigate interactions in ciprofloxacin (CIP) adsorption to goethite, hematite, and magnetite at pH 6.0. Thermodynamics and the site energy distribution theory (SEDT) were adopted to clarify the complexation types. Using the adsorption results, pH‐dependent interactions were qualitatively elucidated. The thermodynamic data revealed the difference in adsorption mechanisms. With increasing sorbate loading, CIP adsorption to hematite and magnetite was endothermic, and both enthalpy change and entropy change decreased; however, CIP sorption to goethite showed opposite characteristics. The higher adsorption capacity and affinity of CIP to hematite and magnetite than those to goethite were caused by their higher site energy of the highest occurring frequency ( E 0 * ) and the temperature‐dependent average site energy, respectively. The E 0 * on the surface of goethite was about 17–19 kJ mol −1, where E 0 * values of hematite and magnetite were 20–26 kJ mol −1 . When temperature increased from 289.15 to 308.15 K, the high‐ and low‐energy site densities for three iron minerals changed by −32 to 167% and by −36 to 223%, respectively. The different thermodynamic and SEDT results indicated that CIP adsorption mechanisms to goethite and hematite/magnetite were mainly outer‐ and inner‐sphere complexation, respectively. The findings of this study reveal the adsorption mechanisms and are helpful in evaluating the transport of antibiotics in soils containing typical iron minerals. Core Ideas: Ciprofloxacin adsorption was exo‐/endo‐thermic to goethite/hematite and magnetite. Δ G increased while Δ H and Δ S decreased on minerals with ciprofloxacin concentration. The changes of high‐ and low‐energy adsorption sites with temperature were quantified. Heterogeneity and average of site energy were correlated with active site density.